The Necessity of Development and Implementation of Twins Registry in Iran - Hamidreza Abtahi; Marsa Gholamzadeh; Leila Shahmoradi (مجله انفورماتیک سلامت و زیست پزشکی, 2018)
Introduction: In the last three decades, national twins registries have been developed throughout the world with the aim of studying unique genetic characteristics and the possibility of determining the genotypic effects. This structured information can provide new vision in relation to the causes of diseases and psychological disorders. Method: In this analytic review, all active twins registries around the world were identified and their properties were examined by researchers. Additionally, PubMed, Scopus, Web of Science, Science Direct and Google Scholar databases were searched based on our search strategy. Finally, 69 articles related to the aim of study were selected. Results: Thirty founded national twins registries were analyzed in terms of the country, the goal and type of study, time of foundation, methods for information gathering, biobank samples, outcomes and unique characteristics. Conclusion: Considering the valuable results of twins registries in other countries, high potential of production of scientific documents and obtaining valid results and on the other hand, and the presence of more than 1,300,000 existing twins in Iran, developing a national Iranian twins registry and creating a biobank could be lead to creating one of the biggest national twins registries in the world. This, in turn, could be resulted in producing scientific publications in relation to the identification of cause of different diseases and mental disorders.